Modulus of Elasticity and Tensile Strength for Laminated Zinc Composite Plate - Ismail, Noorli (Journal of Structural Monitoring and Built Environment, 2024)
The concept behind preparing the laminated zinc composite plate is based on the principles of Metal Matrix Composites (MMC) and utilizes recycled zinc sourced from construction sites. The objective of this study is to fabricate a composite plate with a target modulus of 10 GPa, ensuring superior stiffness and load-bearing capabilities. The composite plate is constrained to a maximum thickness of 2 mm. The composite plate design involves a single type of material zinc sheets arranged in multiple layers and bonded using epoxy adhesive glue. A total of seven (7) zinc sheet layers were combined. The epoxy adhesive consists of two components, resin and hardener, mixed in a 1:1 ratio. This combination forms a strong bond between the zinc sheets, enabling the composite plate to withstand high pressure without delamination. Previous studies have reported that zinc plates exhibit excellent mechanical properties, including ultimate strength (120 MPa), compressive strength (110 MPa), tensile strength (120 MPa), and flexural strength (100–150 MPa). Tensile tests conducted in the laboratory yielded maximum stress values of 348 MPa, 320 MPa, and 250 MPa for three different zinc composite plates. In conclusion, after thorough analysis and calculations, the average modulus of elasticity for the zinc sheet composite was determined to be 14.3 GPa, exceeding the initial design target of 10 GPa.